P07.08.B Surgical management of recurrent lower-grade gliomas: analysis of oncological and functional outcomes and associated factors. (5th September 2022) - Gay, L; Rossi, M; Sciortino, T; Conti Nibali, M; Simonelli, M; Navarria, P; Rudà, R; Soffietti, R; Bello, L
Abstract: Background: Presently, there are no clear evidence-based recommendations for the surgical management of progressive or recurrent lower-grade gliomas (LGGs). In our work, we evaluated the oncological (PFS, OS) and functional (neurological, neuropsychological, quality of life evaluation) outcomes of a series of LGGs treated in a 5-year period. The aim was to identify clinical, imaging, and molecular factors, associated with better outcomes, to be implemented in the treatment decision making process. Material and Methods: In our retrospective analysis, 738 recurrent LGGs were included (follow-up 7.9 years; IQR:6-9); 550 were surgically treated, 495 with open resection (with brain mapping techniques), and 55 with tumor biopsy (with frameless stereotactic technique). Results: Overall, 521 patients (70.6%) recurred. Of those treated with open resection 63.5% relapsed. Tumor progression was histologically confirmed in 72.5% of cases, no valuable tumor (effect of treatment) in 27.5% of cases (particularly in cases previously treated with RT and CHT), histo-molecular conversion (astrocytoma instead of oligodendroglioma diagnosis) in 7.5% of cases, malignant transformation in 38.7% of cases. Among the clinical (patient functional status, previous PFS, previous EOR, previous CHT and duration of CHT, previous RT), imaging (type of recurrence, i.e. typical versus atypical, speed of growth, contrast enhancement), and molecular (IDH, codeletion, ATRX, MGMT, tumor grade, CDNK status) factors analyzed, longest PFS of recurrent tumors was associated with patient functional status, previous PFS, previous EOR, speed of growth (>6 mm/year), atypical type of recurrence, tumor grade, presence of codeletion, and CDNK status. Best functional outcome associated with surgical resection, EOR, and tumor grade; worst functional outcome with RT and malignant transformation. Longest OS associated with previous EOR, surgical resection, tumor grade, presence of co-deletion. Malignant transformation was associated to previous EOR. Among patients submitted solely to tumor biopsy, changes in MGMT methylation status and in IDH status were observed in 65.3% and 5% of cases, respectively. Modification in IDH status was associated with atypical (distant) type of recurrence. New histo-molecular profile helped in the treatment decision making process. Conclusion: Surgical resection of recurrent LGGs is associated with longer PFS and OS. Tumor biopsy should be considered, when surgery considered unfeasible, to tailor adjuvant treatment.